2009
DOI: 10.3389/neuro.08.016.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early psychosocial deprivation on the development of memory and executive function

Abstract: This study investigated the effects of early institutional care on memory and executive functioning. Subjects were participants in the Bucharest Early Intervention Project (BEIP) and included institutionalized children, children with a history of institutionalization who were assigned to a foster care intervention, and community children in Bucharest, Romania. Memory and executive functioning were assessed at the age of 8 years using the Cambridge Neuropsychological Test and Automated Battery (CANTAB). As expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
198
2
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 232 publications
(232 citation statements)
references
References 18 publications
23
198
2
9
Order By: Relevance
“…This susceptibility may be due to its high density of glucocorticoid receptors and dopaminergic projections (Pani, Porcella, & Gessa, 2000), and the fact that it is one of the last brain regions to reach maturity (Gogtay & Thompson, 2010; Gogtay et al., 2004). In support of this, deficits in functions mediated by PFC and cortico‐striatal networks, such as attention, working memory and other executive functions, have also been reported in individuals who have experienced childhood trauma (Bos, Fox, Zeanah, & Nelson, 2009; Colvert et al., 2008). …”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…This susceptibility may be due to its high density of glucocorticoid receptors and dopaminergic projections (Pani, Porcella, & Gessa, 2000), and the fact that it is one of the last brain regions to reach maturity (Gogtay & Thompson, 2010; Gogtay et al., 2004). In support of this, deficits in functions mediated by PFC and cortico‐striatal networks, such as attention, working memory and other executive functions, have also been reported in individuals who have experienced childhood trauma (Bos, Fox, Zeanah, & Nelson, 2009; Colvert et al., 2008). …”
Section: Introductionmentioning
confidence: 69%
“…Although the decreased D2 receptor binding (CC genotype) has been associated with poorer performance on timed attention tests in previous studies (Slagter et al., 2012; Yang et al., 2004), the main effect of genotype in our study emerged in two‐way ANCOVA with childhood trauma category as another fixed factor, showing that CC homozygotes who have experienced childhood trauma perform more poorly on a sustained attention test, compared to those who have not experienced childhood adversity. The effect of early life stress on cognitive outcomes has been repeatedly demonstrated in earlier studies (Bos et al., 2009; Colvert et al., 2008), and it is to be expected due to the long maturation period of the PFC (Gogtay & Thompson, 2010; Gogtay et al., 2004) and high concentration of glucocorticoid receptors and dopaminergic projections in the PFC (Pani et al., 2000). However, it should be noted that the genotype–early life stress interaction was only found in the RVP test.…”
Section: Discussionmentioning
confidence: 99%
“…EF has been thought of as comprising three overlapping component skills: cognitive flexibility/rule shifting, updating/working memory, and inhibitory control (30). Previous laboratory studies with older PI children have shown reduced performance on each of these components: cognitive flexibility (11), working memory performance (11,12,15), and inhibitory control (13,15,31). Additionally, there are extensive reports that PI children show attention deficits and hyperactivity symptoms that persist into adolescence (32,33), which could signal long-term difficulties with EF.…”
Section: Ef In Postinstitutionalized Childrenmentioning
confidence: 99%
“…Behavioral studies have shown that children who experienced early life deprivation but were adopted into nurturing homes exhibit reduced EF performance later in childhood, between the ages of 6 and 14 y (11)(12)(13)15), usually measured at least 3-4 y after adoption. EF has been thought of as comprising three overlapping component skills: cognitive flexibility/rule shifting, updating/working memory, and inhibitory control (30).…”
Section: Ef In Postinstitutionalized Childrenmentioning
confidence: 99%
See 1 more Smart Citation